Phage Therapy Is Effective in a Mouse Model of Bacterial Equine Keratitis - Furusawa, Takaaki; Iwano, Hidetomo; Hiyashimizu, Yutaro; Matsubara, Kazuki; Higuchi, Hidetoshi; Nagahata, Hajime; Niwa, Hidekazu; Katayama, Yoshinari; Kinoshita, Yuta; Hagiwara, Katsuro; Iwasaki, Tomohito; Tanji, Yasunori; et al. (Applied and environmental microbiology, 2016)
Bacterial keratitis of the horse is mainly caused by staphylococci, streptococci, and pseudomonads. Of these bacteria, Pseudomonas aeruginosa sometimes causes rapid corneal corruption and, in some cases, blindness. Antimicrobial resistance can make treatment very difficult. Therefore, new strategies to control bacterial infection are required. A bacteriophage (phage) is a virus that specifically infects and kills bacteria. Since phage often can lyse antibiotic-resistant bacteria because the killing mechanism is different, we examined the use of phage to treat horse bacterial keratitis. We isolated Myoviridae or Podoviridae phages, which together have a broad host range. They adsorb efficiently to host bacteria; more than 80% of the ΦR18 phage were adsorbed to host cells after 30 s. In our keratitis mouse model, the administration of phage within 3 h also could kill bacteria and suppress keratitis. A phage multiplicity of infection of 100 times the host bacterial number could kill host bacteria effectively. A cocktail of two phages suppressed bacteria in the keratitis model mouse. These data demonstrated that the phages in this study could completely prevent the keratitis caused by P. aeruginosa in a keratitis mouse model. Furthermore, these results suggest that phage may be a more effective prophylaxis for horse keratitis than the current preventive use of antibiotics. Such treatment may reduce the use of antibiotics and therefore antibiotic resistance. Further studies are required to assess phage therapy as a candidate for treatment of horse keratitis. IMPORTANCE Antibiotic-resistant bacteria are emerging all over the world. Bacteriophages have great potential for resolution of this problem. A bacteriophage, or phage, is a virus that infects bacteria specifically. As a novel therapeutic strategy against racehorse keratitis caused by Pseudomonas aeruginosa , we propose the application of phages for treatment. Phages isolated in this work had in vitro effectiveness for a broad range of P. aeruginosa strains. Indeed, a great reduction of bacterial proliferation was shown in phage therapy for mouse models of P. aeruginosa keratitis. Therefore, to reduce antibiotic usage, phage therapy should be investigated and developed further.